O plano municipal de educação na região da associação dos municípios do Alto Uruguai catarinense – AMAUC: embates e contradições - Campos, Marcia Farinella Soares de (Universidade do Vale do Rio dos Sinos, 2020)
The induction of educational policies by International Organizations has interfered in the elaboration of policies that consider the needs of Brazilian schools. Thus, action by the State, focusing its actions on partnerships and maintaining control of policies in a clear regulatory model, opens space for external agents to engage in the development of these policies in Brazilian municipalities. The methodology used by MEC is triggered at SASE / DICOPE, where the creation of the Technical Assistance Network in the states unfolds in Tripartite Committees, demonstrating an articulated planning, aiming to guarantee the effectiveness of the Municipal Education Plans within the stipulated period. In this sense, the clashes and contradictions present in the process of preparing Municipal Education Plans were constituted as the central axis of this study after the approval of law 13,005 / 2014, such action triggered locally by Educational Assessors through planning articulated by MEC. Historical Dialectical Materialism made up the theoretical dimension, the qualitative methodological approach and the technical resources used involved research in legislation and semi-structured interviews, in addition to authors in the area who supported the data analysis. The empirical field used the municipalities in the region of the Association of Municipalities of Alto Uruguai Catarinense - AMAUC, namely: Arabutã, Alto Bela Vista, Concórdia, Ipira, Ipumirim, Irani, Itá, Jaborá, Lindóia do Sul, Peritiba, Piratuba, Presidente Castello Branco, Seara and Xavantina. In the development of the research, a municipal director refused to participate in the research, so the corpus of the study was made up of 13 (thirteen) municipalities in addition to the Educational Evaluator responsible for the region and the National Plan Coordinator at MEC. The results of the study point to documents that were built urgently, with little popular participation, focusing education professionals on making the process effective. The absence of the community in the discussions of the document, the tight deadline and the hiring of external consultants also illustrate the findings of the study. The clashes took place in the exchange of evaluators, in the mismatched guidelines and in the need to follow a ready model without considering existing documents.
Keywords: Políticas públicas educacionais; Plano municipal de educação; Rede de assistência técnica; Comitê tripartite; Avaliador educacional; Educational public policies; Municipal plan of education; Technical assistance network; Tripartite committee; Educational evaluator; ACCNPQ::Ciências Humanas::Educação